Estudo dielétrico dos compósitos Bi2Fe4O9(1 – x)-CaTiO3(x) e Bi2Fe4O9(1 – x)-BiCu3Ti3FeO12(x) e suas aplicações como antena ressoadora dielétrica - Silva, Ana Maria Amaral (2025)
The demand for ceramic materials with specific properties applicable to communication technologies has led to the study and development of composites with characteristics such as high dielectric constant, low loss or thermal stability at a resonant frequency. Bismuth iron oxide Bi2Fe4O9 is a ceramic material with multiferroic properties that has applications such as catalysis, optical absorption and gas sensors. Composites with different proportions of mass addition (20%, 40%, 60% and 80%) between Bi2Fe4O9 and calcium titanate (CaTiO3) and between Bi2Fe4O9 and the ceramic matrix BiCu3Ti3FeO12 were prepared by the solid-state reaction method. The synthesis of the desired phase was confirmed by X-ray diffraction analysis and the composites were properly characterized, as well as micrographs of the sample surfaces were made and the series with CaTiO3 was also characterized by Raman spectroscopy. In both series the matrix underwent decomposition with formation of several phases. The density of all samples was obtained through pycnometry, where the pure matrix and all compositions presented relative densities below 81%. The dielectric characterization in the microwave region showed that the addition of CTO increases the ε values of the matrix and decreases the electrical loss values. The presence of BCTFO in bulk in the matrix also leads to higher ε values while maintaining the same order of magnitude of the tangent loss. The numerical simulation data indicates a satisfactory performance of the antennas with radiation efficiency values between 72 and 97%. The two series showed that it is possible to synthesize a composite with the two proposed ceramic materials whose temperature coefficient value of the resonant frequency is close to zero.